THE TEACHING PROFESSION IN THE DIGITAL AGE: A LITERATURE REVIEW ON TEACHER COMPETENCIES, THE CHALLENGES OF TECHNOLOGICAL TRANSFORMATION, AND STRATEGIES FOR EDUCATORS’ PROFESSIONAL DEVELOPMENT - Busnawir; Mohammad Ahmad Bani Amer (Review of International Journal Education and School Leadership, 2026)
The digital age has fundamentally transformed the paradigm of the teaching profession, demanding comprehensive transformation in teachers’ competencies, the management of technological transformation challenges, and innovative professional development strategies. This literature review examines four core teacher competencies (pedagogical, professional, social, and personal) integrated with digital literacy through the TPACK and DigCompEdu frameworks, demonstrating that teachers in the digital age act as facilitators of adaptive learning and technology innovators. The analysis reveals key challenges including the digital divide, limited rural infrastructure, teacher resistance to adaptation, and administrative burdens that hinder the implementation of hybrid learning. Effective professional development strategies include practice-based ICT training, professional learning communities, microlearning platforms, and public-private collaboration for universal connectivity. Policy implications include flexible curriculum reform based on the ‘Merdeka Belajar’ initiative, equitable investment in digital infrastructure, and the strengthening of national digital literacy. These findings underscore the urgency of a holistic approach to cultivating competitive 21st-century educators, with recommendations for longitudinal empirical research to measure the effectiveness of AI and the metaverse in Indonesian education.